The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Respiratory Monitoring in Mechanical Ventilation 2021
DOI: 10.1007/978-981-15-9770-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Mechanics

Abstract: SIGLAS ABREVIATURAS C. vital Capacidad vital C.S. respiratorio Compliance del sistema respiratorio CaO2 Concentración arterial de oxígeno CcO2 Contenido capilar de oxígeno CO2 Dióxido de carbono COVID-19 Enfermedad causada por el coronavirus 2019 (por sus siglas en inglés) Cpulmón "Compliance" o distensibilidad del pulmón CRF Capacidad residual funcional CvO2 Contenido venoso de oxígeno Cw Caja torácica por sus silgas en inglés

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 309 publications
(124 reference statements)
1
4
0
Order By: Relevance
“…The present study revealed median Crs values below the those reported as normal in other studies 2,4 and established a correlation with variables such as height and age, along with sex, to construct a predictive equation for Crs. However, the model exhibited a low R 2 value.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The present study revealed median Crs values below the those reported as normal in other studies 2,4 and established a correlation with variables such as height and age, along with sex, to construct a predictive equation for Crs. However, the model exhibited a low R 2 value.…”
Section: Discussionsupporting
confidence: 69%
“…In this context, the prediction of lung mechanics is crucial for its rst estimation or during daily measurements. This value can aid in assessing the impact of diagnoses of acute conditions (atelectasis, Acute Respiratory Distress Syndrome [ARDS], Acute Obstructive Abdomen, pneumonia and pulmonary congestion) or chronic conditions (Chronic Obstructive Pulmonary Disease [COPD], pulmonary brosis, obesity and sequelae of major infections) 2,4,13 . Additionally, it can help in determining better PEEP levels to relationship between elastic pressure and lung expansibility (using decremental PEEP maneuver 14 ), thereby guiding the safe selection of ventilation parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COs are considered to be an intrinsic cause of automatic ventilator triggering; moreover, they may be visible on ventilator signal waveforms during apnea, and they are thought to be due to changes in the cardiac output and physical movement of the heart during each ventricular systole (Aarrestad, 2020;Mac-Intyre et al, 2021). The change in intrathoracic pressure caused by airflow and the displacement of adjacent lung tissue play a role in automatic ventilator triggering (Noujeim et al, 2013;Zhou et al, 2021). This phenomenon can occur both in a patient with brain death and in a patient without brain death.…”
Section: Introductionmentioning
confidence: 99%